A Genetic Susceptibility Mechanism for Major Depression. Issue 23 (June 2015) - Wang, Yanfang; Sun, Ning; Li, Suping; Du, Qiaorong; Xu, Yong; Liu, Zhifeng; Zhang, Kerang; Konuk., Numan
<x xml:space="preserve">Abstract</x> Abstract Major Depression (MD) is a highly inherited psychiatric disorder. The norepinephrine transporter (NET) gene plays important role in pathophysiology of MD. This study attempted to examine the relationship between polymorphisms of NET gene and MD. Patients with MD and healthy controls were recruited and subgrouped. The T-182C and G1287A polymorphisms of NET gene were genotyped by direct sequencing. The genotypic and allelic frequencies were compared using the Pearson χ2 analysis. The linkage disequilibrium was analyzed using the UNPHASED program. Significant differences in genotypic and allelic frequencies of T-182C polymorphism were observed between MD subgroups and controls. When referenced by TT genotype, the OR value increased gradient from TC to CC genotype; when referenced by T allele, the odds ratio value of C allele also increased. Compared with those having both −182 T/T and 1287 G/G genotypes, in patients with MD, early-onset MD, and MD with suicide concept group, the −182 C/C and 1287 G/A combinatorial genotype has significant risk; yet in patients with MD family history, the −182 C/C and 1287 A/A combinatorial genotype has significant risk. Different combinations of T-182C and the G1287A polymorphisms of NET gene might increase morbidity risk of MD subpopulations.